Nutritional value and chemical composition of pastures of peanut forage or red clover - doi: 10.4025/actascianimsci.v35i1.12692 - Ricardo Lima de Azevedo Junior; Clair Jorge Olivo; Cláudia Marques de Bem; Priscila Flores Aguirre; Mauricio Pase Quatrin; Suélen Capa de Ávila (Acta Scientiarum. Animal Sciences, 2012)
With this study, we aimed at evaluating the nutritional value and chemical composition of forage legume intercropping with elephant grass (EG) + spontaneous growth species (SGS) + annual ryegrass (AR) + peanut forage (PF), as treatment T1; and EG + SGS + AR + red clover (RD), as T2. The EG was planted in 4-m spaced rows. The annual ryegrass was planted between the EG rows during the cool season; the RC was sowed and the PF was preserved. The experiment was performed between October 2009 and April 2010, with six grazing cycles. Samples of forage legume was collected, under simulated the grazing, to determine the levels of organic matter (OM), crude protein (CP), neutral detergent fiber (NDF), organic matter in situ digestibility (OMISD), total phenols (TF), total tannins (TT), and condensed tannins (CT). The mean values of OM, CP, NDF, OMISD, TF, TT and TC were 90.8, 20.96, 48.38, 86.68, 1.92, 1.42 and 1.39%; and 91.84, 21.41, 41.36, 85.18, 1.90, 1.31 and 0.17% for peanut forage and red clover, respectively. Higher values (p ≤ 0.05) were observed in the level of CT of peanut forage.